2004
DOI: 10.1016/j.crvi.2003.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Individual vocal differences of the coo call in Japanese monkeys

Abstract: We investigated individual vocal characteristics of the coo call in Japanese monkeys. The goal of the study was to determine which parameters are individual discriminators (for individuals of different ages and sexes) and to test whether those differences were similar for individuals of same age and sex. A discriminant analysis realized on eight individuals pointed out that three parameters (call duration, start and end frequencies of the fundamental component) differentiated individuals efficiently and was va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…These functions should result in an emphasis on the acoustic features characteristic of particular individuals. Acoustic individuality in vocalization has been demonstrated in a wide range of primate species using field investigations and laboratory experiments [e.g., mouse lemur Microcebus murinus, Zimmermann & Lerch, 1993; cotton-top tamarin Sayuinus oedipus, Snowdon et al, 1983; common marmoset Callithrix jacchus, Jones et al, 1993; tufted-ear marmoset Callithrix kuhli, Jorgensen & French, 1998; spider monkey Ateles geoffroyi, Chapman & Weary, 1990; squirrel monkey Saimiri sciureus, Boinski & Mitchell, 1997; rhesus monkey Macaca mulatta, Rendall et al, 1998; Japanese macaque Macaca fuscata, Ceugniet & Izumi, 2004; and chimpanzee Pan troglodytes, Mitani et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…These functions should result in an emphasis on the acoustic features characteristic of particular individuals. Acoustic individuality in vocalization has been demonstrated in a wide range of primate species using field investigations and laboratory experiments [e.g., mouse lemur Microcebus murinus, Zimmermann & Lerch, 1993; cotton-top tamarin Sayuinus oedipus, Snowdon et al, 1983; common marmoset Callithrix jacchus, Jones et al, 1993; tufted-ear marmoset Callithrix kuhli, Jorgensen & French, 1998; spider monkey Ateles geoffroyi, Chapman & Weary, 1990; squirrel monkey Saimiri sciureus, Boinski & Mitchell, 1997; rhesus monkey Macaca mulatta, Rendall et al, 1998; Japanese macaque Macaca fuscata, Ceugniet & Izumi, 2004; and chimpanzee Pan troglodytes, Mitani et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence for individual distinctiveness in vocalizations was obtained in the squirrel monkey (Boinski & Mitchell 1997), in the baboon (Owren et al 1997), the rhesus monkey (Rendall et al 1996(Rendall et al , 1998Owren & Rendall 2003), the Japanese macaque (Ceugniet & Izumi 2004a) and the cotton-top tamarin (Weiss et al 2001). Owren et al (1997) showed that the spectral energy peak (formant) patterning varied with caller identity in baboon grunts, and constituted the strongest grouping variable.…”
Section: Perception Of Identity Information In Voicementioning
confidence: 99%
“…In this sense, acoustic marking can be especially advantageous when studying sensitive or threatened species (Gilbert et al 1994). Most individual recognition studies via acoustic signals have been carried out in territorial birds, but the technique has been used also in other taxa such as amphibians and numerous mammals (Ceugniet and Izumi 2004). In the latter group, however, the problematic identification of calling individuals due to variation associated to social factors has limited the applicability of the method (Mitani and Brandt 1994).…”
mentioning
confidence: 99%